1430. Novel Transmission of Burkholderia pseudomallei from a Freshwater Aquarium to a Human — Maryland, 2019. (31st December 2020) - Dawson, Patrick; Duwell, Monique M; Thompson, Ruth J; Crum, David A; Blythe, David; Jacobs, Ruth; Elrod, Mindy G; Gee, Jay E; Liu, Lindy; Blaney, David D; Weiner, Zachary; Bower, William A; et al.
Abstract: Background: Nearly all U.S. cases of melioidosis, a potentially fatal disease caused by Burkholderia pseudomallei, are associated with travel to endemic areas. In September 2019, a patient in Maryland with no international travel history developed melioidosis and whole genome sequencing (WGS) of the patient's clinical isolate showed it clustered most closely with isolates from Southeast Asia. CDC and Maryland Department of Health (MDH) investigated possible sources of B. pseudomallei exposure to identify the source and route of transmission and evaluate risk to others. Methods: MDH interviewed the patient and household members during October–December 2019. In consultation with CDC, MDH conducted environmental sampling of the patient's home including drains, faucets, potted and ground soil, imported products, and two freshwater aquariums. Samples were tested for B. pseudomallei at CDC by PCR and culture. B. pseudomallei isolates underwent WGS and were analyzed along with a reference panel of geographically diverse, publicly available genomes. Results: Three environmental samples, all from aquarium #2, were positive for B. pseudomallei . These isolates matched the patient's clinical isolate by WGS, suggesting the aquarium was the source of exposure. According to interviews, the patient set up both aquariums in July 2019 and all the fish in aquarium #2 died in August 2019. The patient recalled reaching her bare hands and arms into the aquarium in August 2019, one month prior to illness onset. Conclusion: This investigation led to the first documentation of transmission of B. pseudomallei from a freshwater aquarium to a human. Many freshwater ornamental fish are imported from Southeast Asia, so this newly recognized transmission route may have significant implications for the freshwater aquatics trade. Further investigations are underway at the retail location that sold the fish and the commercial vendors that supplied the freshwater animals and plants imported from Southeast Asia. Disclosures: All Authors : No reported disclosures